POLA KOMUNIKASI GURU AKIDAH AKHLAK DALAM PEMBINAAN AKHLAK SISWA YANG BERKARAKTER - Nur Hayati (Jurnal Ilmu Pendidikan dan Kearifan Lokal, 2023)
Many phenomena today are knowledgeable but lacking in morals and civility. Therefore, education needs to develop human morals, because the aim of education is to humanize humans. The decline in morals occurs due to technological advances and the rapid flow of globalization which causes many negative impacts because it is not balanced and accompanied by faith. One thing teachers can do at school is develop students' morals by using good communication patterns. Communication patterns can be interpreted as forms of communication. This research uses descriptive qualitative, namely research that produces descriptive data in the form of written or spoken words from people and observed behavior. The research used uses data collection techniques such as observation, interviews and documentation. Communication patterns of moral belief teachers in developing student morals in class VII A MTs Bina Iman Pasir Belengkong for the 2022-2023 academic year. The communication pattern used by the moral aqidah teacher in coaching the morals of students in class VII A is using varied communication patterns, namely combining the three communication patterns according to the situation that occurs so that the coaching carried out by a teacher goes well even though it is not completely successful.